Sosialisasi Perpajakan Memoderasi Pengaruh Kesadaran Wajib Pajak dan Sanksi Perpajakan Pada Kepatuhan WPOP - Suriambawa, Agus; Ery Setiawan, Putu (E-Jurnal Akuntansi, 2018)
The purpose of this study was to obtain empirical evidence of the effect of taxpayer awareness and the application of taxation sanctions on the compliance of individual taxpayer. The method of determining the sample in this study is accidental sampling, the analysis technique used in this study is by using the Moderated Regression Analysis (MRA) technique. Based on the results of the study show that: 1) Tax payer awareness has a positive and significant effect on individual taxpayer compliance, 2) Tax sanctions have a positive and significant effect on individual taxpayer compliance, 3) Tax socialization is statistically able to moderate the influence of taxpayer awareness on individual taxpayer compliance, and 4) Tax socialization is statistically able to moderate the effect of tax sanctions on individual taxpayer compliance. Keywords : Tax payer compliance, taxpayer awareness, tax sanctions, tax socialization